Digital radiography and PACS - Carter, Christi E.; Veale, Beth L. (Mosby/Elsevier, 2010)
Offers coverage of computed radiography, digital radiography, and PACS. This book explores the differences between conventional and digital imaging systems and how computed and digital radiography systems fit within the radiology department.